DESIGN AND OPTIMIZATION OF ACYCLOVIR LOADED SOLID LIPID NANOPARTICLES: A SUSTAINED RELEASE APPROACH - A, Deevan Paul; B. S, PHUVISAA; S, KIRUTHIKA; ARSATH, MOHAMED; `D, ABIRAMI; K, GOKUL (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aims to develop Acyclovir-Loaded Solid Lipid Nanoparticles (ASLN) prepared through homogenisation and evaluate their efficacy. Methods: ASLN were formulated using Gelucire 43/01, Polyvinylpyrrolidone (PVP), Tween 80, and Stearic acid in varying ratios through solvent evaporation and homogenisation. Lipids and Acyclovir were melted together and then emulsified using a homogeniser. Particle size distribution was assessed by Dynamic Light Scattering (DLS), and Zeta Potential was measured using electrophoretic mobility. The cumulative drug release profile was analyzed to determine sustained release characteristics. Zero-order kinetic modelling was applied to elucidate the release mechanism, indicating diffusion rate-limited drug release. Comparative studies with marketed Acyclovir formulations were conducted to assess efficacy and performance. Results: All formulations exhibited satisfactory characteristics: Particle size of 185.6±4.28 nm, Zeta potential of-24.15±5.43 mV, Polydispersity Index of 0.192±3.11, and Drug Entrapment Efficiency of 77.06±4.3%. In vitro release studies of ASLN formulation F12 showed prolonged drug release (90.88% cumulative release by the 8th hour), in sustained drug availability. Comparative studies highlighted the efficacy of ASLN compared to commercial acyclovir products. The kinetic analysis confirmed zero-order kinetics and diffusion rate-limited drug release for all formulations. Conclusion: In conclusion, the formulation of ASLN using Gelucire 43/01, Polyvinylpyrrolidone (PVP), Tween 80, and Stearic acid produced nanoparticles with favourable characteristics. These included appropriate particle size, zeta potential, and high drug entrapment efficiency. In vitro studies demonstrated sustained drug release, suggesting ASLN as promising carriers for enhancing Acyclovir's therapeutic efficacy.